WW domain-containing oxidoreductase's role in myriad cancers: Clinical significance and future implications. (March 2014) - Gardenswartz, Aliza; Aqeilan, Rami I
The WW domain-containing oxidoreductase (WWOX) gene, encodes a tumor suppressor located on 16q23.1, spanning FRA16D, one of the most active common fragile sites in the human genome, that is altered in numerous types of cancer. WWOX's alteration in these myriad cancers is due to disparate mechanisms including loss of heterozygosity, homozygous deletion and epigenetic changes. In vitro, WWOX has been found to be reduced or absent in numerous cancer cell lines and WWOX restoration has been found to inhibit tumor cell growth and invasion. Wwox knockout mice developed femoral focal lesions resembling osteosarcomas within one month of their life and aging Wwox heterozygous mice have an increased incidence of spontaneous lung and mammary tumors as well as B-cell lymphomas. We herein review WWOX's role that has been unearthed thus far in different types of malignancies, its clinical significance and future implications.